Analisis Pengaruh Keterbukaan Ekonomi Terhadap Pertumbuhan Ekonomi di Indonesia - Zebua, Merlin Kristin; Idris, Idris; Ariusni, Ariusni (Universitas Negeri Padang, 2024)
This research aims to determine and analyze the influence of economic openness on economic growth in Indonesia. This research uses time series data from 1993-2023 sourced from the Central Statistics Agency, Bank Indonesia, Bank International For Settlements, and World Bank. The results of the study reveal that (1) trade openness has a negative and significant effect on economic growth in Indonesia, (2) Foreign Investment and the real exchange rate have a positive effect, (3) The real exchange rate has a negative and insignificant effect on economic growth in Indonesia.